A QUALITATIVE STUDY OF EMPLOYEE WORK LIFE CONFLICT ON RSUP PROF.R.D.KANDOU MANADO - Mokoginta, Firtalia .; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Abstract: Hospital is one of the important aspect for people in the big city. Hospital plays an important role in preventing disease and providing rehabilitation service to people. Incurrent rapidly growing consumer-oriented health industry, qualityhas become the integral part. This research aims to find out To analyze the Role of Employee Work-Life Conflict in R.S Prof Kandou Manado. Type of this research is qualitative method, the sample size will be 10 employee of RSUP. Prof Kandou. The results show that employees at RS. Prof Kandou think that they are sacrificing their time with family for their work in hospital, employee of RS. Prof Kandou feels they need more time to handle employee work-life conflict. Recommendation for RS. Prof Kandou should maintain and improve the good sign of objectivity and support toward employee who feels burden with employee work-life conflict that they feel.ÂÂKeywords: employee work-life conflict.